IQ variations consequent to speech and language therapy among hard of hearing children - AR, Vasudha (Journal of All India Institute of Speech and Hearing, 1972)
Many western studies have been reported comparing the hard of hearing and normal groups with reference to mental development. One group of such studies have pointed out that the Hard of Hearing as a group are about two years retarded mentally as compared with the normal (Pintner and Reamer, 1920; Myklebust et al. 1960). But according to some other group of studies that there is no significant difference in intelligence between normal and the Hard of Hearing (Levine, (963). In spite of this controversy, with the weight of evidence from the subsequent studies there appears a general agreement that the Hard of Hearing as a group show a functional lag atleast by two years